Implantação de inovações curriculares no interior da escola: a perspectiva da gestão - Carvalho, Esther de Almeida Pimentel Mendes (2019)
This dissertation is inserted in the research field of New Technologies at the postgraduation program in Education and Curriculum from Pontifícia Universidade Católica de São Paulo. Its objective is to analyse, from the perspective of school management, the implementation process of curriculum innovations at a 70-year-old Brazilian private school from 2017 to 2019. Its specific goals are: to describe the elements of curriculum that underwent significant changes in the institution between 2017 and 2019; to analyse the curriculum innovations in relation to the invariables time, space and the relationship with knowledge; and to identify the elements of school management that foster curriculum innovation. This dissertation follows a qualitative approach and applied action research from the narrative of the manager-researcher who identified the essential elements that defined the changes and is aimed to conceive new paths for development. The analysis of the data shows that the institution, in its two branches, underwent curriculum innovations in the categories time, space, relationship with knowledge, and on its evaluation system. From these statements, the work brings an analysis on school management and its role on curriculum innovation considering the following dimensions: power relationships and the decision process; its role on the implementation phases, on motivation and on the characteristics of the organisational culture changes; and the development of both people and infrastructure, while maintaining purpose and translating it into demands. The main conclusion of the research is that a manager’s performance creates room for innovation to thrive. For that, it is necessary to develop their own creativity, converging three elements: motivation, expertise and creative thinking to go beyond boundaries and search for new possibilities. Among them, motivation on its intrinsic nature stands out. It is necessary to aim for balance between understanding the school’s organisational culture and respecting its timing, while at the same time creating demands for a movement in the direction of innovation. It is critical to think about the current culture and to project the culture that one aims to achieve, knowing that the manager himself or herself is also a part of it. The subjectivities are present, including the ones about the manager. As important as being open to experiences, processes and people outside the organisation, or even more important than that, the manager has to be vigilant to see the knowledge and the internal competences